Modeling Manure Quantity and Quality in Finland - Luostarinen, Sari; Grönroos, Juha; Hellstedt, Maarit; Nousiainen, Jouni; Munther, Joonas (Frontiers in Sustainable Food Systems, 2018)
Data on manure quantity and quality is a prerequisite for planning manure management and regulation. It is the basis for directing manure use into more efficient and environmentally sound actions and for fulfilling the targets of nutrient recycling in circular economy. Manure data is often scarce, old or badly documented. Some collect it by sampling and analysis, others with calculation systems / models. In Finland, both options are used. The farmers need to have their manure analyzed at least every five years. The resulting analyzed data from the farms can be combined into a statistics on manure quality. However, this dataset has major shortcomings, such as difficulty to identify different animal categories. Thus, a model called the Finnish Normative Manure System was developed. Technically the system works well and its biggest challenges are related to the vast amount of background data needed. There are still data gaps e.g. in bedding use and cleaning water additions and a need to update the excretion calculations. To assist development of such models, international harmonization of the methods would be beneficial. As such manure data is usually the basis for emission inventories and burden sharing, harmonization would also place farms and countries in a more equal position in international contracts on emission reduction. In this paper, the challenges related to manure data provision are discussed in reflection to the experiences gained during the development of the Finnish Normative Manure System.